FEMVERSTING DALAM IKLAN: KAMPANYE #LIVEWITHOUTLINES OLAY INDONESIA - Hakim, Almira (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The term femvertising emerged in the 1980s and was used by brands and advertisers as an attempt to get involvedin supporting the spread of the feminism movement. On the other hand, femvertising was utilized as an attempt bycompanies to form new branding under the guise of supporting women. This research examines the femvertisingmovement of Olay anti-aging products with the tagline #LiveWithoutLines which invites women in Indonesia toeliminate the lines made by others to limit ourselves as women. Using Roland Barthes' semiological method, thispaper reveals that Olay's #LiveWithoutLines tagline cannot be considered as part of femvertising but rather bringsdiscourse into a commodity form that does not threaten the prevailing dominant power